Advent Of Omicron: An Attempt to Decode the Third Wave Covid Variant - Iram, Dr Farah; Aditi Vats; Dr. Anisha Raju; Dr. Betina Chandolia; Mohini Gahlot; Dr. Niveditha Hariharan; Dr. Saurav Deka (British Journal of Healthcare and Medical Research, 2022)
Currently, severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has spread worldwide as an Omicron (B.1.1.529) variant, after alpha, beta, gamma, Delta. World Health Organization (WHO) has identified the Omicron variant as a variant of concern due to its heavily mutated nature. Phylogenetically, this variant with more than 50 mutations is very different from other variants. With an average doubling time of two days, the Omicron variant spreads rapidly. However, it has been milder than the Delta. Although previous infection and vaccination do not protect against infection with Omicron, they do appear to protect against hospitalization and severe disease. It is likely that Omicron will have enormous indirect effects, such as lockdowns, restrictions, travel bans, economic losses, infections of healthcare workers, and an overwhelming of healthcare facilities. However, as with previous variants, Omicron's direct effects are expected to be mild. Nevertheless, the indirect effects on mental, physical, and social health may be considerable. It is recommended to for all the people to follow the COVID-19 behaviours. In this review, we focused on the emergence, severity, genomics, effectiveness of vaccines, and treatment and management strategy against the Omicron variant, which will be helpful for further investigation of a new variant of SARS‐CoV‐2.